Befizel, Learning Physics by Using Puzzle as Learning Media Innovation - Muslikhah, Umi; Rahmasari, Lita (Sebelas Maret University, 2016)
Learning media has a very important role in learning process of students. BEFIZEL is one of learning media innovation. Due to the design of collaboration on BEFIZEL childrens games, technology and material physics puzzle design that is packed in. By using befizel as learning media will give a new color in the learning process. BEFIZEL consists of puzzle board (batteries, LED: Light-Emitting Diode, switches, cables and PCB, Printed Circuit Board) and design drawing. BEFIZEL can stimulate memory and intelligence of the learners so that learners can easily understand the material in the design puzzle.